Antara Paradigma Dan Realita: Sebuah Rekonstruksi Pendidikan Islam Di Era Kekinian - Arsyadana, Adin (STAI Miftahul Ula Nganjuk, 2017)
The quest for a new paradigm of Islamic education will never cease in the ever-changing and evolving age. However, it does not mean that the idea of ââseeking a new paradigm of education is reactive and defensive, that is, to answer and defend the truth after a challenge. Islamic education must be a powerful force for dealing with a more crucial life discourse. Reflection of thinking and formulation of Islamic education issues must breathe the current (up to date). Islam must be strived to shift the paradigm that is oriented to the past (medieval) to the future-oriented paradigm, which diverts from an educational paradigm that only preserves progress, to an educational paradigm that pioneers progress